Factors influencing reproductive performance in a range of network situations - Thorpe, W.R.; Coulibaly, L.; Defly, A.; D'Ieteren, G.D.M.; Feron, A.; Grundler, G.; Hecker, P.; Itty, P.; Maehl, J.H.H.; Mawuena, K.; Morkramer, G.; Mulungo, M.; et al. (1988)
The effects of trypanosome infection and of other factors on parturition interval were evaluated using records for parturitions, which occurred between January 1984 and December 1986 at the Network sites of Avetonu, Boundiali and Mushie. For Mushie some intervals, calculated using parturitions occurring in early 1987, were also included. Mean litter sizes of sheep at Avetonou and Boundiali were very similar, 1.15 and 1.18, respectively. In Boundiali but not in Avetonou, lambing interval was affected significantly (p<0.05) by trypanosome infection post-partum. Trypanosome infection pre-partum did not affect lambing interval at either site. Apart from the effect of year-season of parturition in Boundial, other systematic environmental effects were not significant sources of variation affecting lambing interval. The least square means for calving interval are 424 days at Avetonou (the shortest), 515 days at Mushie (the longest) and 488 days at Boundiali (intermediate). At each of the three sites cows with trypanosome infection post-partum had longer calving intervals that unaffected cows, but only reached significance (P<0.05) in Avetonou. At each of the sites there was a trend for shorter calving intervals with higher PCV. The effect reached statistical significance (p<0.01) at Mashie.